PELAYANAN INFORMASI PUBLIK PADA DINAS KOMUNIKASI DAN INFORMASI KABUPATEN DONGGALA - Ade Irma (KINESIK, 2021)
Pillars of democracy, transparency and good governance are the objectives of public information services carried out, through Law No. 14 of 2008 on Public Information Disclosure. The form of service organized by the Government is a service in an effort to meet the needs of the public or the community. Communication, Public information is information generated, stored, managed, sent, and / or received by a public body, this research is a qualitative approach, a research paradigm to describe events, locus research located in the Department of Communication and Informatics Donggala Regency, this study uses Informants as many as 4 (four) people, using the theory of Pararusman, et al .Tjiptnono, 1996) there are five dimensions in assessing the quality of services or services, namely, Tangibles, Realibility, Responsiveness, Assurance, Emphathy. 1) Tangibles; reflected in physical facilities, equipment, personnel and communication materials have not been effective and optimal.2) Realibility, i.e. lack of accuracy or lack of reliable information. Responsiveness: lack of sensitivity to respond to information. 4) Assurance; Knowledge is less effective and efficient. 5) Emphathy. Still lacking, officers in the process of public information services